Towards a UML profile for modeling WAP applications - Soto De Giogis, Ricardo (2005)
UML (Unified Modeling Language) is one of the most used languages to specify and document informatics applications. However, UML is a generalpurpose language, so it often lacks of elements to model and represent concrete concepts of specifics domains. As a solution, OMG (Object Management Group) has created the profiles, a mechanism to extend the syntax and semantics of UML to express more specific concepts of certain application domains. In this work we present a UML profile for modeling WAP (Wireless Applications Protocol) applications. The main goal of the proposed profile is to extend UML to provide specifics elements (labeled classes, stereotypes, tagged values and constraints) that allow software developers to modelWAP applications. The expressiveness of the UML diagrams allows modeling important stages of the process of common applications; nevertheless, the modeling process of WAP applications is still a too specific domain that can be hardly dealt with in its entirety without extending the language. In the process exists navigational, design and construction issues that cannot be modeled using the traditional elements of UML. However, by using the specific elements created by the proposed profile, these issues can be completely solved, and even a greater expressiveness can be obtained.